(untitled) (Journal of Engineering, 2024)
Foam concrete is a type of concrete that is widely used in civil engineering as a high-quality building material with low weights and usually low compressive strength. Improving the compressive strength is the main objective of this paper by supplying this type of concrete with different proportions from carbon fibers. This study included preparing an experimental mixture to produce foam concrete consisting of optimal ratios of water-to-cement ratio (0.35), sand-to-cement ratio (1:1.5), and superplasticizer (1.8 %). The appropriate dosage of foaming agent was selected to obtain lightweight foam concrete with an appropriate compressive strength of up to 17.4 MPa and a target density of (1300-1350) kg/m3 after 28 days. Adding carbon fibers gave a 1 % highest compressive strength estimated at 9.77 % but the flow rate decreased by about 8.55 % compared to the reference mixture after 28 days. The results indicate that adding fibers contributed to increasing the compressive strength of foam concrete, but it negatively affected the flow rate.